Tectonic Inheritance Following Failed Continental Subduction: A Model for Core Complex Formation in Cold, Strong Lithosphere. Issue 5 (22nd May 2019) - Biemiller, James; Ellis, Susan; Mizera, Marcel; Little, Timothy; Wallace, Laura; Lavier, Luc
Abstract: Inherited structural, compositional, thermal, and mechanical properties from previous tectonic phases can affect the deformation style of lithosphere entering a new stage of the Wilson cycle. When continental crust jams a subduction zone, the transition from subduction to extension can occur rapidly, as is the case following slab breakoff of the leading subducted oceanic slab. This study explores the extent to which geometric and physical properties of the subduction phase affect the subsequent deformation style and surface morphology of post subduction extensional systems. We focus on regions that transition rapidly from subduction to extension, retaining lithospheric heterogeneities and cold thermal structure inherited from subduction. We present numerical models suggesting that following failed subduction of continental crust (with or without slab breakoff), the extensional deformation style depends on the strength and dip of the preexisting subduction thrust. Our models predict three distinct extensional modes based on these inherited properties: (1) reactivation of the subduction thrust and development of a rolling‐hinge detachment that exhumes deep crustal material in a domal structure prior to onset of an asymmetric rift; (2) partial reactivation of a low‐angle subduction thrust, which is eventually abandoned as high‐angle, "domino"‐style normal faults cut and extend the crust above the inherited thrust; and (3) no reactivation of the subduction fault but instead localized rifting above the previous subduction margin as new rift‐bounding, high‐angle normal faults form. We propose that the first mode is well exemplified by the young, rapidly exhumed Dayman‐Suckling metamorphic core complex that is exhuming today in Papua New Guinea. Key Points: Strength and dip of inherited subduction thrust controls extensional style following rapid transition from subduction to extension Tectonically inherited lithospheric structure can promote metamorphic core complex formation in cold, strong lithosphere Inherited subduction‐related lithosphere conditions can explain the formation and exhumation of the Dayman‐Suckling core complex